Purification, structural elucidation, and in vitro antitumor effects of novel polysaccharides from Bangia fuscopurpurea - Jingna Wu; Xiaoting Chen; Kun Qiao; Yongchang Su; Zhiyu Liu (Food Science and Human Wellness)
A water-soluble polysaccharide, designated BFP-3, was isolated from Bangia fuscopurpurea by hot water extraction, anion-exchange, and size-exclusion chromatography and tested to determine its antitumor activity. The structural characteristics of BFP-3 were investigated by chemical and spectroscopic methods, including partial acid hydrolysis, methylation analysis, one- and two-dimensional nuclear magnetic resonance, and gas chromatography-mass spectrometry. The results showed that BFP-3 was mainly comprised of rhamnose, arabinose, mannose, glucose, and galactose. Moreover, the weight-average molecular weight of BFP-3 was estimated to be approximately 333 kDa. The backbone of BFP-3 was primarily composed of repeating 5-α-l-Araf-1→(4-α-d-Glcp-1)4→4,6-β-d-Manp-1 units, and the side chains consisted of repeating β-d-Galp-1→(4-β-d-Galp-1)4→4,6-β- d-Galp-1→3,4-α-l-Rhap, β-l-Arap-1→(3-β-d-Galp-1)3, and β-l-Arap-1 units. Counting Kit-8 assays revealed that BFP-3 significantly inhibited the proliferation of A2780, COC1, SKOV3, HO-8910, and OVCAR3 ovarian cancer cells in vitro, indicating that BFP-3 could have potential applications in the treatment of ovarian cancer.